Perbedaan dan Persinggungan Konseptual antara Falsafah Syariah dan Falsafah Tasyri’: Conceptual Differences and Intersections between Falsafah al-Sharī‘ah and Falsafah al-Tashrī‘ - Syamsul Ilmi; Rahmatiah HL; Lomba Sultan; Noercholis Rafid. A (QISTHOSIA : Jurnal Syariah dan Hukum, 2025)
Philosophical studies, particularly in Islamic legal philosophy, continue to generate dynamic intellectual discourse among scholars of Islamic law. One significant area of inquiry concerns the relationship between the philosophy of sharia (falsafah al-sharī‘ah) and the philosophy of legislation (falsafah al-tashrī‘). The urgency of distinguishing and understanding the points of convergence between these two concepts becomes increasingly evident when Islamic law is confronted with contemporary challenges. This study focuses on two main objectives: (1) comparing the scope, objects, and approaches of falsafah al-sharī‘ah and falsafah al-tashrī‘; and (2) providing a clear conceptual framework to prevent overlap and terminological confusion between these two concepts in the study of Islamic legal philosophy. This research employs a qualitative library-based method using normative-theological and conceptual-comparative approaches. Data were collected from classical and contemporary Islamic legal literature and analyzed using descriptive-analytical techniques. The findings indicate that falsafah al-sharī‘ah is oriented toward legal values, objectives, and wisdom (maqāṣid), whereas falsafah al-tashrī‘ focuses on the legislative process and the methodology of legal formulation. Both intersect within the domains of maqāṣid al-sharī‘ah and uṣūl al-fiqh, which function as a bridge between ideal values and the normative formulation of Islamic law. This study contributes conceptually to clarifying the epistemological foundations of Islamic legal philosophy and its relevance to the development of contemporary Islamic law.